Analyzing Organizational Structures for Shift Workers in Mining Division Unit Pertambangan Tanjung Enim (UPTE) PTBA - Muhammad Ihsan; Aurik Gustomo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The objective of this research is to determine the most suitable shift work model for supervisory positions at PTBA-UPTE, with the aim of improving productivity, employee well-being, and cost-effectiveness. The study utilized a mixed-methods design, incorporating focus group discussions with industry experts, benchmarking practices, and the Analytical Hierarchy Process (AHP) to support multi-criteria decision-making. Three alternative models were assessed: the existing 3-shift rotation, an extended-hours 2-shift model, and a hybrid system combining elements of 2-shift and non-shift schedules. Based on the AHP analysis, the hybrid model emerged as the most advantageous, demonstrating a 35% reduction in required manpower and stronger alignment with both operational efficiency and workforce wellness objectives.